Improvement of soybean productivity through the application of organic, inorganic, and biological fertilizers in acid soils - Henny Kuntyastuti; Sri Ayu Dwi Lestari; Didik Sucahyono; Sutrisno Sutrisno (Brawijaya University, 2022)
Acid dry land can become a centre for soybean production through improved cultivation techniques and the use of improved varieties that are acid-tolerant. In connection with this problem, research has been carried out to evaluate the effect of the application of organic fertilizers, inorganic fertilizers, and biological fertilizers on soybean productivity in acid soils. The experiment was conducted in a screen house at Iletri, Malang, East Java, using acid dry soil from Banten, West Java. The soybean seed used in this research was Wilis variety. The evaluated treatments were a combination of types and quantities of nutrient-rich organic fertilizer with acid formula (Santap-M), NPKS Phonska inorganic fertilizer, and biological fertilizer (Iletrisoy Rhizobium and Pseudomonas sp P-solubilizing bacteria, both were Iletri collections). The results showed that the addition of organic and inorganic NPKS fertilizers on acid soils could increase soybean productivity and the population of P-solubilizing bacteria Pseudomonas sp. The recommended alternative technology component for improving soybean productivity and Banten acid soil is a combination of 1500 kg Santap-M nutrient-rich organic fertilizer + 150 kg Phonska/ha. The results of this study add to the positive list that use of organic fertilizers and inorganic fertilizers NPKS is an alternative option that needs to be considered for sustainable soybean cultivation in acid dry land.